(3TQM GdQSGdI GdHgGFjI aj GdMSGHs - (3YeQ Hf CMeO, GdeGFj GdMdjs
(3ChdgG (B:s
(3jGef YLR Yfi JVGYa fYeg CbdGe CagGe GdYbdGA CeG HYO ajbhd hJfHjgGJ Ydi QeR GdeHGMK GdeYVdI ef GdQSGdI GdHgGFjI ai GdMSGH s
(3BNQgG (B:s
(3heYdhe Cf GdNGQL ef GdeGA NeSI ai eLehY CKfi YTQ PQGYkG hfUa hgh GdeWdhH hGdMeO ddg QH GdYGdejf JeJ MGTjI GdHgGFjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi GdeLehY hbajI dedG YHO Gddg GdYHOdi Ydi ChdGOg hjQLY JGQjNgG Edi SfI (B1239 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs